The first 24 hour bilirubin level as a predictor of hyperbilirubinemia in healthy term newborns. - Rina Triasih, Rina Triasih (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2002)
Background: The practice of early discharge in healthy term newborns results in difficulty for recognition, follow-up and early treatment of hyperbilirubinemia, the most common cause of readmission in term newborns.Objectives: The aim of the study was to determine the ability of first 24 hours total and unbound bilirubin levels in predicting hyperbilirubinemia in healthy term newborns in the first week of life. Methods: The first 24 hours and 5th day of total and unbound bilirubin were measured in 84 healthy term newborns. The total bilirubin level was measured spectrophotometrically whereas unbound bilirubin level was determined by peroxidase-oxidation method. Hyperbilirubinemia was defined as serum total bilirubin of a 12.9 mg/dL or serum unbound bilirubin of a 0.5 mg/dL after 24 hours of life.Results: A correlation between first 24 hours and 5th day of total bilirubin was found (r= 0.53) with a regression equation: Y (total bilirubin day 5) = 4.69 + 1.15 X (total bilirubin first 24 hours). In unbound bilirubin (r= 0.31), the regression equation was Y (unbound bilirubin day 5) = 0.13 + 0.95 X (unbound bilirubin first 24 hours). The relative risk of newborns whose first 24 hours total bilirubin of a 4.5 mg/dL and becoming hyperbilirubinemia was 12 (95% CI = 2.9 - 48.4), and newborns whose unbound bilirubin of a 0.09 mg/dL was 9.5 (95% CI = 1.2-77.4).Conclusions: Total bilirubin level a 4.5 mg/dL in the first 24 hours can predict the occurance of hyperbilirubinemia in the first week of life inthe term newborns.Key word: fullterm newborn, hyperbilirubinemia, prediction, total bilirubin, unbound bilirubin